Study of Students' Interest and Motivation in Participating in the Pencak Silat Brotherhood of Loyal Heart (PSHT) Ranting Ngronggot - Mabarok, Moh Rizky; Weda; Sugito (CV. Nusantara Sporta, 2024)
This research examines the interest and motivation of students at PSHT Ranting Ngronggot in participating in pencak silat activities. The research used a qualitative descriptive approach with the subject of ten PSHT students in Ranting Ngronggot. Data was collected through observation, interviews and documentation. The research results show that students' intrinsic interests include developing self-defence skills, instilling moral values, and seeking personal challenges. Extrinsic interests are driven by support from the surrounding environment and family. Intrinsic motivation comes from internal interests such as physical achievement and character development, while extrinsic motivation comes from family encouragement and social relationships. In conclusion, students' interests and motivation, both intrinsic and extrinsic, are important factors that encourage their participation in PSHT in Ranting Ngronggot.